Promising behavior change techniques for climate-friendly behavior change - a systematic review - Lisa Masciangelo; Susanne Lopez Lumbi; Michel Rinderhagen; Claudia Hornberg; Michaela Liebig-Gonglach; Timothy Mc Call; Timothy Mc Call (Frontiers Media S.A., 2024)
IntroductionBesides societal and governmental actions to mitigate greenhouse gases, individual behavioral changes are also urgently needed to limit global temperature rise. However, these individual changes have proven to be difficult to achieve in the general population.MethodsWe conducted a systematic review in five electronic databases with the aim of systematically depicting the content of interventions that promote climate-friendly behavior in individuals and households in high- and upper-middle-income countries.ResultsWe included 25 studies. The analyses included identification of the used Behavior Change Techniques (BCTs) and comparison of their promise ratio. Across our three outcome categories energy consumption, water consumption, and mobility the most frequently used BCT categories are not the ones that are most promising in terms of behavior change.DiscussionBased on these results, our recommendation for climate change mitigation interventions is to include components that provide concrete instructions on how to perform the desired behavior (shaping knowledge), setting goals and commitments (goals and planning), substituting undesired behavior, and practicing desired behavior (repetition and substitution). Other reviews with similar aims use different wordings, definitions, or degrees of detail in their intervention component labelling which makes it difficult to compare the results. We recommend to use a standardized classification system, like the BCT taxonomy in combination with the promise ratio, which this study has shown to be a suitable tool to classify applied intervention techniques and give an indication of successful techniques.